Socialization of strategies to become a safe legal indonesian migrant worker (PMI) In East Lampung - Putri, Ria Wierma; Tristiyanto; Triyono, Agus; Putri, Yunita Maya; Zakiyyah, Rizqi; Lindasari (Community Service for Sustainable Community Journal, 2024)
Background: East Lampung Regency ranks first in Lampung Province and ninth nationally as a sending region for migrant workers (PMI), with 75,311 people. Despite contributing significantly to the migrant workforce, the region faces numerous civil law challenges, including cases of employment termination, passport detention, undocumented workers, and overstays, making it a critical area for addressing migrant worker issues. Methods: This study employed a qualitative approach, analyzing secondary data from government reports, legal records, and migrant worker case studies in East Lampung. Interviews with key stakeholders, such as government officials, legal experts, and migrant worker advocacy groups, were also conducted to understand the root causes and impacts of these civil law cases. Findings: The research found that East Lampung's prominence as a PMI sending region correlates with an increase in civil law cases involving migrant workers. Issues like lack of proper documentation and legal protection are key factors contributing to the high incidence of cases such as termination of employment and passport detention. The study also identified gaps in policy implementation and support systems for migrant workers, both before and after departure. Conclusion: East Lampung Regency's status as a leading PMI sending region is accompanied by significant legal challenges for migrant workers. Strengthening legal frameworks, improving migrant worker documentation, and providing pre-departure training on legal rights are essential for reducing civil law cases and ensuring better protection for workers.  Novelty/Originality of this study: This study is unique in highlighting the specific legal issues faced by migrant workers from East Lampung Regency. It provides a comprehensive analysis of the underlying causes of civil law cases and offers recommendations for policy improvements to enhance the protection and welfare of migrant workers from this region.